Fundamentals of Entrepreneurship ENT300 Abram Cement Enterprise / Nick Mattaaari Jefri... [et al.] - Jefri, Nick Mattaari; Donny, Helda; Hadenan, Marina; Gunsalam, Ecca Sandra (2011)
After doing extensive research on the business opportunity available in MATANG area, our group decided to specify our business in selling cement. Our group has come up with the business plan of partnership whereby our organization's name, known as ABRAM CEMENT TRADING. In order to establish our business plan, all aspects including the four major of business establishment such as administration, marketing, operation, and finance are seriously taken into consideration.